2021
DOI: 10.3390/ijerph18094668
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Mental Health among Children/Adolescents, Their Parents, and Young Adults during the First COVID-19 Lockdown in Switzerland

Abstract: The present study aimed to assess various stressful situations and the psychological impact of the first COVID-19 pandemic lockdown among youths in Switzerland. We included samples of 1627 young adults aged 19–24 from the Swiss Youth Epidemiological Study on Mental Health and 1146 children and adolescents aged 12–17 years and their parents. We assessed symptoms of various mental health problems, internet use, and perceived stress during the first COVID-19 lockdown. In the analyses, data were weighted to be rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
136
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 57 publications
14
136
0
5
Order By: Relevance
“…This is contradicted in two previous studies by Huang and Zhao ( 2020 ) and Wang et al ( 2020 ); when evaluating the psychological impact of the uncontrolled spread of COVID-19, they realized that the manifestations of anxiety and psychological outbreaks were more common especially in the younger population who used social networks for a longer time (Huang and Zhao 2020 ; Wang et al 2020 ). On the other hand, pandemic uncertainty and confinement created considerable levels of stress in young people, especially women, in Switzerland (Mohler-Kuo et al 2021 ). It was further shown that misinformation fueled by rumors and conspiracy theories led to physical harassment and violent attacks against healthcare professionals and people of Asian origin in 28% of the results shown in this review.…”
Section: Discussionmentioning
confidence: 99%
“…This is contradicted in two previous studies by Huang and Zhao ( 2020 ) and Wang et al ( 2020 ); when evaluating the psychological impact of the uncontrolled spread of COVID-19, they realized that the manifestations of anxiety and psychological outbreaks were more common especially in the younger population who used social networks for a longer time (Huang and Zhao 2020 ; Wang et al 2020 ). On the other hand, pandemic uncertainty and confinement created considerable levels of stress in young people, especially women, in Switzerland (Mohler-Kuo et al 2021 ). It was further shown that misinformation fueled by rumors and conspiracy theories led to physical harassment and violent attacks against healthcare professionals and people of Asian origin in 28% of the results shown in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from systematic reviews showed that the COVID-19 pandemic has had an important impact on adolescents' mental health [20,21]. Anxiety, depression, loneliness, and poor sleep quality are the most common psychological problems [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…More than 80% of young people in Europe use social networks and spend an increasing amount of their time consuming digital media [1][2][3][4][5]. EU Kids Online [6] states that more than half of the children report that they use smartphones or mobile phones daily or almost daily, several times a day, or all the time.…”
Section: Introductionmentioning
confidence: 99%